Influence of Ethylene Diamine Capping on the Structural and Optical Properties of Hydrothermally Synthesized Cadmium Sulphide Nanoparticles - Nirmala Jothi, N.S.; Gunaseelan, R.; Sagayaraj, P. (Asian Journal of Chemistry, 2011)
One dimensional nanoparticles of cadmium sulphide were prepared using ethylene diamine assisted solvothermal synthesis. X-ray diffraction result confirms that the nanorods are of hexagonal structure and the selected area electron diffraction identifies its single crystalline nature. The sample was characterized by UV-VIS absorption, photoluminescence spectrum, scanning electron microscopy, transmission electron microscopy and thermal analysis. The UVVIS absorption spectrum indicates the narrow size distribution of the cadmium sulphide nanorods. The absorption band edge is seen shifted to 490 nm than the bulk material and the corresponding band gap is found to be 2.53 eV. The photoluminescence emission peak is detected around 503 nm. From SEM and EDAX analysis, the morphology of the aggregates and the composition of the obtained product are identified. The TEM micrographs show that the cadmium sulphide nanorods have well defined morphology and high crystalline quality with narrow size distribution of lengths and widths. The thermal behaviour of the as prepared nanopowder was studied by thermogravimetric analysis.